STUDY ON THE IMPACT OF ANTHROPOGENIC FACTORS ON THE CHANGES IN THE HYDROLOGICAL REGIME OF THE AMU DARYA RIVER AND ITS CONSEQUENCES FOR WATER RESOURCES (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
This study is dedicated to investigating the impact of anthropogenic factors on the transformation of the Amu Darya River's flow in the second half of the 20th century and the early 21st century. Based on a detailed analysis of hydrological data, calculations were performed for six key time periods, taking into account the years when hydraulic structures were put into operation. The conducted research allowed for the identification of trends in river flow changes under the influence of human activity, as well as the distinction of the main stages of the most intense changes. The results obtained play an important role in understanding the processes of water resource changes in the region and in developing scientifically grounded approaches to their effective management.
Keywords: Amu Darya River; anthropogenic impacts; hydrological monitoring; river discharge; agricultural irrigation; hydrological dynamics; water resource management